Understanding the current backlash against LGBTIQ+ rights through the lens of heteroactivism: A case study of the International Organization for the Family’s transnational norm diffusion on Twitter - Strand Cecilia; Eriksson Åsa; Svensson Jakob (Nordic Journal of Media Studies)
A new generation of transnational anti-gender actors are framing themselves as human rights champions and protectors of the rights of the “natural family”. To better understand these actors’ norm diffusion, including their re-styling of anti-gender narratives in contemporary iterations of heteroactivism and its potential threat to LGBTIQ+ rights, in this article we analyse the social media tactics of a key transnational anti-gender actor: the International Organization for the Family (IOF). The analysis is focused on the organisation’s Twitter (now X) account and we draw on theories of network media logic, connective action, and connective emotions. Two periods of activism – the first a low-intensity period in 2021 and the second a high-intensity period in 2022 – were purposefully selected for the analysis. In this article, we identify differences between the two periods, noting that the period covering the flagship event, the World Congress of Families (WCF) in 2022, was markedly less LGBTIQ-hostile and adversarial than the first period. IOF thus appears to be inspired by heteroactivist frames during the WCF and abides by logic that should trigger user interaction and content spreading. The lack of interactions and engagement with IOF Twitter content in either period indicates the need for more research on which logics apply to anti-gender audiences. We discuss the findings and what they may imply in a context like Sweden, a country whose self-image as a global champion for women’s and LGBTIQ+ rights may make it ill-equipped to counter the onslaught of transnational actors’ norm entrepreneurial activities.